Evaluating the Correlation of Fasting Blood Sugar, Glycated Hemoglobin with the Hearing Loss - Hwisa, Sara; Alnaeli, Ghada; Faraj, Mofeda; Elmessawi, Nahed M; Salem , Ghada; Soliman, Namat; Kubas, Iman; Habhab, Laila; Abu Gharara , Hanadi (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives: Hearing loss is one of the most prevalent disabilities. Factors that can be controlled are linked to hearing loss. Diabetes, which can potentially lead to hearing loss during cases of high blood sugar levels, appears to be a contributing factor to hearing loss. This study aimed to determine the relationship between fasting blood sugar (FBS) and glycated hemoglobin (HbA1c) with hearing loss. Method: This was a cross-sectional study conducted on two groups: the study sample consisting of patients with both diabetes and hearing loss, and the control sample comprising non-diabetic individuals with hearing loss. The study was carried out at the Sabratha Residential Clinic, Surman Clinic Al-Kubra, and Surman General Hospital between April 12, 2022, and October 25, 2023. During this period, a questionnaire was prepared, and a "Pure Tone Audiometry" hearing test was performed in the planning room to assess the hearing status of participants in both the study and control groups. Results: The study involved 80 participants, of whom 44 (55%) were male and 36 (45%) were female, aged 25-65 years. Compared to the control group, the study group had significantly higher fasting blood sugar (FBS: 202.13 ± 48.13 vs. 81.38 ± 9.50, p<0.001) and glycated hemoglobin (HbA1c: 9.48 ± 2.1 vs. 4.25 ± 0.59, p<0.001) levels, The study group exhibited greater hearing impairment in the left ear (56.90 ± 22.94 vs. 44.40 ± 28.13, p=0.031), but the difference in right ear hearing loss was not statistically significant (53.33 ± 24.47 vs. 44.025 ± 28.41, p=0.121). HbA1c (r=0.239, p=0.027) and FBS (r=0.216, p=0.033) both showed significant positive correlations with hearing loss. Conclusion: This study found that type 2 diabetes mellitus adversely affects hearing, with sensorineural hearing loss positively correlating with HbA1c and FBS levels. These findings indicate that poor glycemic control is associated with an increased risk of hearing impairment in this patient population. الخلفية والأهداف: فقدان السمع هو أحد أكثر الإعاقات انتشارًا. ترتبط العوامل التي يمكن التحكم فيها بفقدان السمع. يبدو أن مرض السكري، الذي يمكن أن يؤدي إلى فقدان السمع أثناء حالات ارتفاع مستويات السكر في الدم، هو عامل مساهم في فقدان السمع. هدفت هذه الدراسة إلى تحديد العلاقة بين سكر الدم الصائم (FBS) والهيموجلوبين السكري (HbA1c) وفقدان السمع. الطريقة: كانت هذه دراسة مقطعية أجريت على مجموعتين: عينة الدراسة المكونة من مرضى مصابين بمرض السكري وفقدان السمع، وعينة التحكم المكونة من أفراد غير مصابين بالسكري يعانون من فقدان السمع. أجريت الدراسة في عيادة صبراتة السكنية، وعيادة صرمان الكبرى، ومستشفى صرمان العام بين 12 أبريل 2022 و25 أكتوبر 2023. خلال هذه الفترة، تم إعداد استبيان، وتم إجراء اختبار السمع "Pure Tone Audiometry" في غرفة التخطيط لتقييم حالة السمع للمشاركين في كل من مجموعتي الدراسة والتحكم. النتائج: شملت الدراسة 80 مشاركًا، منهم 44 (55%) من الذكور و36 (45%) من الإناث، تتراوح أعمارهم بين 25 و65 عامًا. وبالمقارنة مع مجموعة التحكم، كان لدى مجموعة الدراسة مستويات أعلى بكثير من سكر الدم الصائم (FBS: 202.13 ± 48.13 مقابل 81.38 ± 9.50، p <0.001) والهيموجلوبين السكري (HbA1c: 9.48 ± 2.1 مقابل 4.25 ± 0.59، p <0.001)، وأظهرت مجموعة الدراسة ضعف سمع أكبر في الأذن اليسرى (56.90 ± 22.94 مقابل 44.40 ± 28.13، p = 0.031)، ولكن الفرق في فقدان السمع في الأذن اليمنى لم يكن ذا دلالة إحصائية (53.33 ± 24.47 مقابل 44.025 ± 28.41، p = 0.121). أظهر كل من HbA1c (r=0.239, p=0.027) وFBS (r=0.216, p=0.033) ارتباطات إيجابية كبيرة مع فقدان السمع. الاستنتاج: وجدت هذه الدراسة أن مرض السكري من النوع 2 يؤثر سلبًا على السمع، حيث يرتبط فقدان السمع العصبي الحسي بشكل إيجابي بمستويات HbA1c وFBS. تشير هذه النتائج إلى أن ضعف التحكم في نسبة السكر في الدم يرتبط بزيادة خطر ضعف السمع في هذه الفئة من المرض